Improvement of air change rate through roof design configurations using numerical method - Moey, Lip Kean (2019)
Malaysia is a tropical country with hot and humid weather, and low wind speed. Therefore, the natural air ventilation in the building may not be sufficient resulted in the discomfort and bad hygienic for the occupants. To improve the natural air ventilation in the building with the limitation of low wind speed, the moderation of indoor air condition with the roof cover shall be considered. The objective of the present study is to investigate the effect of various design configurations of venturi- shaped roof for improvement of a ventilated stairwell. The existing stairwell has five levels with dimensions of approximately 7 × 7 × 25 m (length × width × height), with the flat roof angle of 11˚. Three types of roof namely flat, ellipse, and double ellipse surface roof with roof angle range of 11˚ to 50˚ and incoming wind speed range of 1 – 5 m/s were investigated. Computational fluid dynamics (CFD) software has been employed in this study. The simulation was conducted using ANSYS FLUENT to obtain the flow characteristics and velocity distribution. Validation of results have been done through open circuit low speed wind tunnel experiments on flat and ellipse venturi-shaped roof at 11 ˚. The model was scaled down by a factor of 50 so it can be tested inside the 1× 1 m closed test section. The incoming wind speed was controlled by using pitot-tube with a monitor Testo 510. The air speed at various opening positions of the model was measured by the hot wire anemometer. It was found that RNG k-ε model closely resembled the trend of those obtained from wind tunnel experiments. Good correlation between the numerical and experimental results was observed (less than 4% average difference). The simulated results showed that the double ellipse roof has the highest U/Uref values at roof angle of 11˚. Furthermore, it is found that to enhance the ACH of the existing stairwell, the roof angle is proposed to be at 20° instead of the existing 11°. With this change of roof angle, the ACH of the stairwell can be improved significantly by 32% for incoming wind speed of range 1 – 5 m/s. The results from this study will be useful for designing wind induced ventilation building in hot and humid climate.